Hubungan Hasil Deteksi Dini Diabetes Mellitus Menggunakan Aplikasi Android "DM Personal Screening" Dengan Kadar Gula Darah Acak Pengunjung Puskesmas Janti Kota Malang - Gayatri, Rara Warih; Wardani, Hartati Eko; Katmawanti, Septa (Preventia: The Indonesian Journal of Public Health, 2019)
According to the 2013 Riskesdas results, in Indonesia there were 0.6% of the population aged 15 years and over or around 1 million people who actually felt the symptoms of DM in the last month but it was not certain whether they had diabetes or not (Ministry of Health, 2014). In addition, according to Riskesdas 2013, there are more than 8 million people with diabetes mellitus who have not been diagnosed (MOH, 2014). Early detection efforts need to be enforced both by using identification of risk factors and their symptoms and signs as well as throughphysical examination in the form of measuring blood sugar levels. The purpose of this study was to determine the relationship between the results of early detection of DM disease using the android application "DM Personal Screening" with an examination ofrandom blood sugar levels of visitors to the Janti Health Center in Malang. This study used a correlative research design with a cross-sectional design and was conducted at the Janti Health Center in Malang. The sampling method used was a purposive sampling method with a total sample of 30 visitors. The measured variable is the result of early detection using the android application "DM Personal Screening" with random blood sugar levels. Data collection techniques using a questionnaire and Glucometer Easy Touch brand. Data analysis was performed using univariate and bivariate statistical analyzes. The measurement results show the relationship of random blood sugar levels with the measurement of DM personal screening is p value = 0.277. Conclusion was that there was no significant relationship between measurement results using KGDA examination with DM personal screening (p value -0.277).